Learning by nature: the implementation and evaluation of culturally responsive pictorial module of nature tie-dye batik craft / Siti Zuraida Maaruf and Ahmed Waliyuddin Basri - Maaruf, Siti Zuraida; Basri, Ahmed Waliyuddin (Research Management Centre (RMC), 2019)
The aim of thisstudy isto determine the usefulness of Culturally Responsive Pictorial Module ofNature Tie-Dye BatikCraft forteaching and learning the topic ‘Batik Pelangi’in Visual Art Education (VAE). The pictorial module was developed using the ADDIE Model that was supported by Zone of Proximal Development (ZPD) – Scaffolding by Lev Vygotsky (1978). This study usesthe Design Development Research (DDR) approach. The Pictorial Module was evaluated by two expert panels which is one experienced VAE school teacher and one Visual Art senior lecturer at a local university. A purposive sampling consisting of 29 VAE students and one VAE teacher were used in this research to measure their acceptance using the module. Both the responding groups of students and VAE teacher provided positive feedbacks toward learning and teaching using the module. Based on the findings, the Pictorial Module isrelevant and appropriate to be implemented at secondary school level for art education in Malaysia.